Optimalisasi Potensi Wisata Desa melalui Pendekatan SDGs: Studi Kasus Kebun Refugia Magetan, Jawa Timur - Riski Sabila (Athallah Publishing Globalndo, 2025)
This study aims to examine efforts to optimize village tourism potential through the Sustainable Development Goals (SDGs) approach, focusing on the development of the Refugia Garden in Magetan Regency, East Java. The Refugia Garden is a form of ecotourism innovation based on environmental conservation and village community empowerment. Through a descriptive qualitative approach, data were collected through in-depth interviews, participatory observation, and documentation of tourism managers, village officials, and visitors. The results of the study show that the application of the SDGs principles, especially in goal 8 (Decent Work and Economic Growth), goal 11 (Sustainable Cities and Communities), and goal 15 (Terrestrial Ecosystems), has encouraged increased community participation, local job creation, and environmental conservation. The obstacles faced include budget limitations, suboptimal digital promotion, and varying levels of community environmental awareness. In conclusion, the SDGs approach can be an effective framework for developing sustainable village tourism and improving the local economy.